Human Factors on the Flight Deck Safe Piloting Behaviour in Practice - Ebermann, Hans-Joachim.; Scheiderer, Joachim; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
What is for a professional pilot required to fly as safe as possible? Written by pilots the book gives a detailed introduction into the basics of accident prevention in air traffic. Explicit background knowledge as well as detailed listings of safety relevant features in human behaviour are included.
Accident prevention -- Information assimilation and processing -- Human error -- Communication -- Stress -- Decision making -- Leadership and team behaviour -- Fatigue and alertness management -- Recommendation by the German Airline Pilot's Association.
Keywords: Engineering; Computer science; Astronautics; Engineering; Aerospace Technology and Astronautics; User Interfaces and Human Computer Interaction; Industrial and Organisational Psychology; Law of the Sea, Air and Outer Space